Analisis Konseptual Model Pembelajaran Humanistik-Digital pada Madrasah Ibtidaiyah - Claresa Agustini; Reza Amellia; Nova Asvio; Novita Angra; Yosi Yulizah (JURNAL ARMADA PENDIDIKAN, 2026)
Digital transformation in education demands learning innovations that are not only technology-based but also maintain humanitarian and Islamic values. This study aims to conceptually analyze the humanistic-digital learning model in Islamic Elementary Schools (MI) as an effort to integrate the humanistic approach and the use of digital technology. The research method used is a literature review with a qualitative descriptive-analytical approach through the analysis of various relevant and up-to-date scientific sources. The results show that humanistic learning emphasizes the holistic development of student potential, while digital learning provides easy access, flexibility, and an interactive learning experience. The integration of these two approaches in the humanistic-digital model can create student-centered learning, increase learning motivation, develop creativity and critical thinking skills, and strengthen Islamic character and values. This model is also relevant to the demands of 21st-century education that emphasizes critical thinking skills, creativity, collaboration, and communication. Thus, the humanistic-digital learning model can be a strategic alternative in improving the quality of education in Islamic Elementary Schools in the digital era.